Accuracy of a smartphone application using fractal image analysis of pigmented moles compared to clinical diagnosis and histological result. (4th August 2014) - Maier, T.; Kulichova, D.; Schotten, K.; Astrid, R.; Ruzicka, T.; Berking, C.; Udrea, A.
Abstract: Background: Lately, various smartphone applications have been introduced as diagnostic self‐monitoring tools in the evaluation of pigmented moles, but most of these techniques have not been evaluated systematically. Objectives: The purpose of this study was to evaluate prospectively the sensitivity and specificity of a recently developed smartphone application using fractal image analysis for the risk evaluation algorithm in the diagnosis of malignant melanoma compared to clinical diagnosis and histopathological result. Methods: Consecutive patients with melanocytic lesions were recruited and clinical and dermoscopical diagnosis was documented by two dermatologists independently. Imaging and analysis with the smartphone application was performed prior to excision of lesions. The findings were compared to the histological results as gold standard. Results: Of 195 included lesions histopathological analysis revealed 40 melanomas, 42 dysplastic nevi and 113 benign nevi. The sensitivity of the diagnosis melanoma by fractal image analysis using smartphone images was 73%, the specificity was 83% compared to a sensitivity of 88% and specificity of 97% regarding the clinical diagnosis by the dermatologists. Conclusion: The smartphone application using fractal analysis might be a promising tool in the pre‐evaluation of pigmented moles by laypersons, while it is to date inferior to the diagnostic evaluation by a dermatologist.